Біля витоків власності (iсторико-антропологічний начерк) - Писаренко, Г.О. (Археологія і давня історія України, 2020)
Проаналізовано сприйняття володіння у варварському суспільстві за умов несформованого уявлення про особистість. The advantage that the traditional cattle owner (at the beginning of the ХХ century) gave to watching his animals over money that «can only be hidden in a crate» allows us to reach some conclusions regarding the archaic perception of ownership.